Conducta obstétrica en la estenosis mitral moderada en paciente de 30 años con 36 semanas de embarazo. - Miranda Acurio, Sindy Nathaly (2023)
Pregnancy with moderate mitral stenosis presents challenges at Hospital Martín Icaza. A multidisciplinary approach is required to ensure a safe pregnancy. Mitral stenosis is a cardiac condition that hinders blood flow. The research addresses obstetric management and prenatal care. The theoretical framework explores moderate mitral stenosis during pregnancy, including cardiac assessment and imaging studies. The aim is to enhance medical care and maternal-fetal well-being. The research is based on the clinical relevance of moderate mitral stenosis during pregnancy, the need for a multidisciplinary approach, and the improvement of the quality of care. It seeks to identify management strategies to minimize risks. The general objective is to determine appropriate obstetric conduct in pregnant patients with moderate mitral stenosis. Specific objectives include analyzing the incidence of maternal-fetal mortality, identifying risk factors and complications, and characterizing medical recommendations.